Pendidikan Kesehatan dan Pelatihan Senam Brain Gym Bagi Anak Pada Anggota Persekutuan Doa Domus Dei Yogyakarta - Amigo, T.A Erjinyuare; Krisnanto, Paulinus Deny (Universitas Respati Yogyakarta, 2020)
The stage of growth and development of school-age children and preschoolers is a golden age stage. This age stage all development systems including the brain work optimally. Children receive sensory and motoric responses well and are interested in new things. But unfortunately there are some exposure that is not good that should not be done at this age, such as gadgets. Access to using a mobile phone that is felt to be increasingly easy to obtain, in fact it will hamper children's development. Children become lazy to move and just like to play mobile. Although on the other hand, not all applications on mobile phones have a bad impact on children, there are also learning applications that can be used by children. Parents need to be wise in dealing with this situation, so that children do not experience addiction to play mobile phones. The impact of gadget addiction on children can vary from unstable emotions or disturbances to social interaction damage.Â A variety of outdoor and indoor physical activities can be used to divert the attention of children on mobile phones, one of them by doing brain gymnastics or brain gym. Brain gymnastics is a simple exercise that can stimulate brain work activities and is easily done by children. This activity was introduced in the preschool and school age groups by the service team in the community of children who joined the Domus Dei prayer meeting. The children explained that this was their first experience and was an exciting and exciting activity. The children also explained that they would repeat it again at home with both their parents and their caregivers. The purpose of this activity is to increase the interaction of children with the same age as parents and caregivers, and to introduce brain exercise skills to children. The method of activities carried out is counseling and brain exercise training in children. The results of this activity are all children appear active and happy to do brain exercise activities together. Conclusion: Brain gym activity can improve children's interactions with peer groups, and also with parents and caregiversÂ Keywords: Children, Brain Gymnastics